DETERMINATION OF WATER-SOLUBLE VITAMINS CONTENT IN PASTRY USING THE HPLC METHOD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
For the extraction of water-soluble vitamins, 1 g of the sample was accurately weighed and placed into a 50 mL conical flask, followed by the addition of 25 mL of 0.1 N hydrochloric acid (HCl) solution. The mixture was subjected to ultrasonic extraction using a GT SONIC-D3 ultrasonic bath (China) at 60°C for 20 minutes. The standard solutions and sample extract were analyzed using a high-performance liquid chromatography (HPLC) system comprising an LC-40D pump, SIL-40 autosampler, and SPD-M40 photodiode array (PDA) detector, operated with LabSolutions software version 6.92, based on the LC-40 Nexera Lite platform.